(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Since its foundation, a company’s only purpose has been to generate profits for its shareholders. The basic goal of every company, no matter how big or little, is to make more money than it spends. The profitability measurements of the banks that were part of this research were their Return on Equity, Gross Profit Margin ratio, and Return on Assets ratio. When comparing profitability indicators, it is advisable to do so with those of comparable firms or with indicators from the same company’s past. The t-test is used to compare these indicators, which are computed using data obtained from the financial statements of SBI and ICICI bank. The results show that ICICI Bank is doing better than SBI. The results of this study will be useful for academics and scholars who want to delve more into the topic.